CASE STUDY OF TEACHER VIOLENCE AGAINST STUDENTS AT GMIT BOKING ELEMENTARY SCHOOL IN CENTRAL TIMOR REGENCY - Wiwik M. Pingak; Simon S. Sabon Ola; Leonard Lobo (Academic Journal of Educational Sciences, 2020)
This study aims to determine the causes of violence perpetrated by teachers against students at GMIT Boking Elementary School in South Central Timor Regency, East Nusa Tenggara Province. Violence by teachers aims to discipline students who violate the rules in force at school. Violence that is often used by teachers is physical and psychological violence. Physical violence is violence that is done directly such as hitting, slapping, pilling, kicking, pinching, throwing objects that lead to the victim`s body and so on. Physical violence can be done both with bare hands and tools. Psychical violence is violence that tends not to be too real. Psychological violence takes the form of pressure that can reduce mental or brain abilities such as insult and ongoing humiliation to minimize the victim`s self-esteem, screams and threats that are given to bring fear and others. Actions of violence committed by teachers inadvertently with the aim of disciplining students in the school environment can have an enormous impact on the development of students for example, a feeling of confidence in answering questions raised by teachers for fear of being enthusiastic about going to school. To prevent acts of violence in schools can be done to improve the relationship between parents, students and teachers. The key to a good relationship to know the attitudes and character of students and the needs of students at school is the establishment of good communication from the school and parent to avoid violence.